Determinants of Tax Rates and Sanctions on MSME Taxpayer Compliance with Tax Understanding as a Moderating Variable (Empirical Study on MSMEs Taxpayers in the Modern Market) - Septiyana, Rana; Anjarwati, Sri (Dinasti Publisher, 2024)
This research aims to test and analyze the influence of tax rates and tax sanctions on taxpayer compliance with understanding of taxation as a moderating variable.This research aims to test and analyze the influence of Tax Tariffs and Sanctions on Taxpayer Compliance with Tax Understanding as a Moderating Variable (Empirical Study on MSMEs Taxpayers in the Modern Market). The research object is taxpayers of micro, small, medium enterprises (MSMEs) in the Modern Market, especially the culinary sector. The research approach used quantitative using primary data. Data collection was carried out using a questionnaire sheet instrument, by distributing questionnaires to 100 taxpayer MSMEs in Pasar Modern who were engaged in the culinary sector as respondents. Data analysis methods by applying structural equation modeling with the help of the WarpPLS 7.0 tool. The research results show that the tax rate is significantly negative on taxpayer compliance, this shows that the lower the tax rate imposed, the more taxpayers will comply with paying taxes. Tax sanctions do not have a significant effect on taxpayer compliance. Understanding of tax regulations moderates the influence of tax rates on increasing taxpayer compliance. Tax understanding moderates the influence of tax sanctions on increasing MSMEs' taxpayer compliance.